Development of Study Room Blog in Learning Reading Literacy in Elementary School - Otang Kurniaman; Eva Astuti Mulyani; Eddy Noviana; Intan Kartika Sari; Dede Permana; Ela Irnanda; Dzoelqa Wirya Nanda (AL-ISHLAH: Jurnal Pendidikan, 2022)
Life has been changing rapidly. Industrial Revolution 4.0 is developed for people to make a novelty. Education as one of the important parts of people’s life is needed to be prepared for every change to improve the teaching and learning system. This article discusses a study conducted by using developmental research with the development of the 4-D design. This study was a Study Room Blog that was conducted for students who could learn individually based on the previous research and only focused on web development or e-module. The advantage of this Study Room Blog was equipped with an evaluation of students’ scores that could be accessed by teachers. The study involved the students in Elementary School to see their reading literacy. Based on the validator assessment result, the average score from the validation of IT-Technology Experts was 80, which was categorized as good. And the average score from the validation of the Linguist was 81.17, which was categorized as very good. It means that the blog could be used in the teaching and learning activity. After obtaining the validation assessment result from validators, then, this study room blog was applied by using a limited try-out which was applied in two classes, the experimental and control classes. In the experimental class, the average score of pre-test result was 50.71 which increased to the average score of post-test result, 80.9. In the control class, meanwhile, the average score of pre-test result was 60.57 which increased to the average score of post-test result, 75.89. Thus, the use of the study room blog was increasingly effective in learning reading literacy. It means that the study gives a contribution to the teacher and students in increasing reading literacy through the Study Room Blog as an interactive media in teaching and learning activities.